Find the value of:
− 2 0 2 1 + ( − 2 0 1 9 ) + ( − 2 0 1 7 ) + . . . + ( − 1 ) + 2 + 4 + . . . + 2 0 2 2
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We can rewrite the equation as:
( − 1 0 1 0 × 2 − 1 ) + ( − 1 0 0 9 × 2 − 1 ) + ( − 1 0 0 8 × 2 − 1 ) + . . . + ( 0 × 2 − 1 ) + 2 × 1 + 2 × 2 + . . . + 2 × 1 0 1 1
Simplifying, we get: − 1 × 1 0 1 1 + ( − 2 n = 1 ∑ 1 0 1 0 n ) + ( 2 n = 1 ∑ 1 0 1 1 n )
(Explanation of 1st term: there are 1011 terms from 0 × 2 to − 1 0 1 0 × 2 [as 1 0 1 0 − 0 + 1 = 1 0 1 1 ], and the term − 1 appears in all 1011 terms)
Following that, − 1 × 1 0 1 1 + 2 0 2 2
And − 1 0 1 1 + 2 0 2 2
Finally, we get 1 0 1 1
Problem Loading...
Note Loading...
Set Loading...
Rewrite the equation
( 2 − 1 ) + ( 4 − 3 ) + . . . + ( 2 0 2 2 − 2 0 2 1 ) = n = 1 ∑ 1 0 1 1 2 n − ( 2 n − 1 ) = n = 1 ∑ 1 0 1 1 1 = 1 0 1 1